2014
DOI: 10.1371/journal.pone.0105099
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and Stromal MicroRNA Signatures of Columnar Cell Hyperplasia Linking Let-7c to Precancerous and Cancerous Breast Cancer Cell Proliferation

Abstract: Columnar cell hyperplasia (CCH) is the earliest histologically identifiable breast lesion linked to cancer progression and is characterized by increased proliferation, decreased apoptosis and elevated oestrogen receptor α (ERα) expression. The mechanisms underlying the initiation of these lesions have not been clarified but might involve early and fundamental changes in cancer progression. MiRNAs are key regulators of several biological processes, acting by influencing the post-transcriptional regulation of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…MicroRNAs (miRNAs) are small non-coding RNAs that regulate target gene expression by binding to the 3′-untranslated region (3′-UTR) of their target mRNAs, resulting in either mRNA degradation or translational repression 6 7 . MiRNAs play essential roles in many normal biological processes, including cell proliferation, apoptosis, differentiation and stress resistance 8 9 . Accumulating evidence has shown that dysregulation of miRNAs expression is associated with oncogenic transformation.…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small non-coding RNAs that regulate target gene expression by binding to the 3′-untranslated region (3′-UTR) of their target mRNAs, resulting in either mRNA degradation or translational repression 6 7 . MiRNAs play essential roles in many normal biological processes, including cell proliferation, apoptosis, differentiation and stress resistance 8 9 . Accumulating evidence has shown that dysregulation of miRNAs expression is associated with oncogenic transformation.…”
mentioning
confidence: 99%
“…Furthermore, XH regulated T-lymphocyte subsets and improved the immunity of breast cancer patients taking CEF [ 15 ]. Breast hyperplasia, especially of the columnar cells, is the earliest histologically identifiable lesion linked to cancer progression [ 26 ]. Aside from the tumor, XH can treat benign lesions such as breast hyperplasia and prevent transformation into malignancies [ 27 ].…”
Section: Xh Has Antitumor Effects When Combined With Conventional mentioning
confidence: 99%
“…Previous research on let-7c has primarily focused on functions and roles in cancer. It has been shown that let-7c inhibits cancer cell survival by regulating cell proliferation (Bjorner et al, 2014) and apoptosis (Zhan et al, 2013). Recent studies suggest that let-7c is an important regulator of macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%